Stroke volume and cardiac output measurement in cardiac patients during a rehabilitation program: comparison between tonometry, impedancemetry and echocardiography; The International Journal of Cardiovascular Imaging; Vol. 36 - Gonzalez R. A. Represas Alicia (2020, 2020)
Title screen